Unformatted text preview: So a bunch of people have been asking me why they’re getting:
∂x y ∂x
∂y z ∂y
x I probably said in class that one could do the following:
∂y y x The problem here is that there’s nothing on the right hand side that says that
we’re actually holding z constant. When I had derived the Euler chain rule I
did the following:
dy = 0
We can state that z is unchanging by setting dz = 0. Then we can move stuﬀ
∂y dx = −
y x ∂y
= y dy
∂y z Since there is no z and we are holding it constant manually, (∂x/∂y )z = dx/dy .
As you can see, now there’s a −1 present. Crazy huh? 1 ...
View Full Document